A grafted polyhydroxyl small molecule lithium-ion battery silicon anode binder and its preparation method
By developing a silicon negative electrode binder for grafted polyhydroxy small molecule lithium-ion batteries, using ester bonding to connect nanosilicon particles and inducing the generation of fluorine-rich SEI, the volume expansion and SEI instability of silicon negative electrodes in lithium-ion batteries was solved, and the electrochemical performance and cyclic stability of the battery were significantly improved.
Patent Information
- Application Number
- CN202411948967.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-04
AI Technical Summary
The application of silicon negative electrodes in lithium-ion batteries is limited by problems such as volume expansion, powdering, electrical contact failure and unstable solid electrolyte interface (SEI), resulting in rapid attenuation of battery capacity.
A silicon negative electrode binder for grafted polyhydroxy small molecule lithium-ion battery is developed, using silicon nanoparticles, lithium hydroxide, conductive carbon black, oxalic acid and polyacrylic acid, and connecting nanosilicon particles through ester bonding to improve bonding and mechanical stability, and induce the formation of fluorine-rich SEI.
It effectively solves the problem caused by volume expansion of silicon negative electrode during circulation, improves the electrochemical performance and cycle stability of the battery, extends the service life of the battery, and reduces costs.
Smart Images

Figure HDA0005214392570000011 
Figure HDA0005214392570000021 
Figure HDA0005214392570000031
Abstract
Description
Technical Field
[0001] The present application relates to the field of binders, and in particular to a grafted polyhydroxy small molecule lithium ion battery silicon negative electrode binder and a preparation method thereof. Background Art
[0002] Energy is an important foundation and driving force for economic and social development. With the rapid development of society, people's demand for energy is increasing, and the contradiction between energy supply and demand is becoming more and more prominent. In addition, with the gradual depletion of fossil fuels and the continuous intensification of environmental pollution, the exploration and development of clean energy has become the focus of global attention. Clean energy includes ocean energy, hydropower, hydrogen energy, biomass energy, wind energy, geothermal energy and solar energy, which have the disadvantages of intermittent and volatile, and are difficult to use directly. In order to effectively utilize these intermittent energy sources, it is necessary to develop efficient and economical electric energy storage systems (EES). Rechargeable batteries are becoming more and more critical as a suitable choice for EES, which can efficiently convert and stably store clean energy. Among them, lithium-ion batteries have the advantages of high energy efficiency, high power density, light weight and environmental friendliness. They have been widely used in electronic devices such as mobile phones, laptops and digital cameras. In 2023, the global LIB market size will exceed US$64 billion. However, with the rapid development of emerging technologies such as electric vehicles, smart grids, artificial intelligence and virtual reality, lithium-ion batteries are required to have higher energy density while ensuring safety. Therefore, the research on high energy density lithium-ion batteries has attracted great attention from industry and academia in recent years. The theoretical specific capacity of traditional commercial graphite anode is low, and with the increasing maturity of the graphite industry, the actual specific capacity of high-end graphite products has been very close to the theoretical value (372 mAh g -1 ). In this case, it is difficult to further improve the energy density of lithium-ion batteries using traditional graphite negative electrodes.
[0003] Silicon (Si) anode has a high theoretical specific capacity (4200mAh g -1, Li4.4Si), abundant reserves, and low lithium voltage (≈0.4 V vs Li / Li+) have stood out and have been established as one of the most promising negative electrode materials. However, Si negative electrodes still face severe challenges in practical applications. Si undergoes significant volume expansion (up to 300%) during repeated charge and discharge, which can have serious consequences: First, the electrode material Si will be pulverized. As the volume of Si continues to expand, greater stress will be generated inside its particles, resulting in pulverization or even shedding of the particles, which in turn causes a sharp decline in battery capacity. Second, repeated volume expansion will cause electrical contact failure of Si nanoparticles (SiNPs). Since Si is a semiconductor with poor conductivity and cannot quickly and efficiently transmit electrons, additional conductive agents need to be introduced to promote electron conduction. Once the connection between Si and the conductive agent is disconnected, it is difficult for electrons to conduct inside the electrode, which has a serious negative impact on battery performance; third, an unstable and thick solid electrolyte interface (SEI) will be formed. During the first charge and discharge process of lithium-ion batteries, the electrolyte will undergo a reduction reaction on the surface of the negative electrode. This reaction will generate a large amount of inorganic or organic products, which will then be deposited on the surface of the negative electrode, eventually forming a dense passivation film, namely the SEI film. The huge volume changes and surface stress during the charge and discharge process will cause the SEI film formed on the surface of the silicon electrode to rupture frequently, exposing the fresh Si surface to the electrolyte, thereby inducing the continuous growth of the SEI film. This process will continuously consume the lithium source in the positive electrode and electrolyte, damage the coulombic efficiency and capacity of the battery, and have an adverse effect on the overall electrochemical performance of the battery. The above-mentioned many problems have greatly limited the electrochemical performance of the silicon negative electrode and its development process as a negative electrode in practical applications.
[0004] In order to improve the performance of silicon negative electrodes, common strategies include: nano-design of silicon materials, design of silicon electrode composite structures, development of new electrolytes and new binders, etc. Recent studies have shown that although the binder content in the entire electrode is relatively low, it plays a vital role in the integration and structural stability of the entire electrode. The main function of the binder is to form a tight bond between all electrode components and the current collector, while reducing the risk of active material shedding and crushing, while maintaining the integration and integrity of the entire electrode network, thereby ensuring that the battery can maintain a high utilization rate of active materials and excellent cycle stability during the cycle. It can be seen that the development of high-performance binders suitable for silicon negative electrodes is considered to be an urgent problem to be solved to improve the overall performance of silicon negative electrodes.
[0005] The core function of traditional adhesives such as polyvinylidene fluoride (PVDF) and polyacrylic acid (PAA) is to provide strong mechanical support for the electrode structure by firmly bonding the components, thereby ensuring that the battery maintains structural stability during long-term cycling. However, it must be pointed out that many problems such as weak conductivity and unstable SEI still have a very significant adverse effect on the performance of silicon negative electrodes. In view of this, it has become an urgent need to develop new adhesives with multifunctional properties to overcome the above problems. Summary of the invention
[0006] In order to solve the above problems, the present application provides a grafted polyhydroxy small molecule lithium ion battery silicon negative electrode binder and a preparation method thereof.
[0007] The present application provides a grafted polyhydroxy small molecule lithium ion battery silicon negative electrode binder and a preparation method thereof using the following technical solutions: In the first aspect, the present application provides a grafted polyhydroxy small molecule lithium ion battery silicon negative electrode binder, which adopts the following technical solution: A grafted polyhydroxy small molecule lithium ion battery silicon negative electrode binder comprises silicon nanoparticles, lithium hydroxide and conductive carbon black.
[0008] Preferably, oxalic acid is also included.
[0009] Preferably, polyacrylic acid is also included.
[0010] Preferably, the mass ratio of the polyacrylic acid, oxalic acid and lithium hydroxide is 21:(3-9):(4.2-5.4).
[0011] In a second aspect, the present application provides a method for preparing a grafted polyhydroxy small molecule lithium ion battery silicon negative electrode binder, using the following technical solution: A method for preparing a grafted polyhydroxy small molecule lithium ion battery silicon negative electrode binder comprises the following steps: Polyacrylic acid, oxalic acid and lithium hydroxide are dispersed in water, heated and stirred to obtain a LiPOA component; silicon powder, conductive carbon black and anhydrous ethanol are mixed and ground to obtain a composite powder, and the LiPOA component is added to the composite powder and stirred to obtain a binder.
[0012] Preferably, when preparing the LiPOA component, the heating and stirring temperature is 100°C.
[0013] In summary, the present application includes at least one of the following beneficial technical effects: 1. Silicon anode will produce huge volume expansion (>300%) during the cycle, which may lead to particle crushing, loss of electrical contact and unstable SEI, causing rapid capacity decay. The structural design of the present invention effectively solves the problem caused by volume expansion and improves the electrochemical performance of the battery; 2. The current commercial binder polyvinylidene fluoride is connected by weak intermolecular interaction (van der Waals force) and cannot withstand the stress caused by its huge volume expansion during the cycle, which leads to the rapid attenuation of the capacity of the silicon negative electrode battery. The binder prepared in this application can connect nano silicon particles through ester bonding, the process is simple, and the bonding effect is strong; 3. The current binder design function is relatively single, mainly focusing on the basic adhesion effect, which can alleviate the electrode structure collapse caused by Si volume expansion to a certain extent, but problems such as weak conductivity and unstable SEI still significantly affect the performance of silicon negative electrode. The binder designed in the present invention has multiple functions - mechanical stability, interface stability and promotion of lithium ion conduction, which can effectively improve the electrochemical performance of Si negative electrode; 4. During the first charge and discharge process of the battery, the electrolyte undergoes a reduction reaction on the surface of the negative electrode, producing a large amount of inorganic or organic products and depositing them on the surface of the negative electrode, thereby forming a dense passivation film, namely the SEI film. The iterative volume change of SiNPs destroys the SEI layer, resulting in the formation of another SEI layer on the fresh Si surface. This process will continuously consume lithium ions and electrolytes, thereby weakening the Coulomb efficiency in each cycle and eventually exhausting the electrolyte. Therefore, a stable SEI is crucial to the Si negative electrode. Studies have shown that fluorine-rich SEI is strong and has good ion conductivity. The binder designed in the present invention effectively induces the formation of fluorine-rich SEI on the surface of SiNPs, effectively improving the stability of SEI and the lithium ion transfer rate, thereby improving the cycle stability of the silicon negative electrode.
[0014] 5. Pre-lithiation of polyacrylic acid and grafting of oxalic acid can improve the mechanical properties of the binder, and give the binder the function of stabilizing the interface and promoting ion conduction, thereby effectively improving the electrochemical performance of the Si negative electrode. The design of a multifunctional binder can greatly improve the performance of the silicon negative electrode, and develop a new type of multifunctional binder that can not only improve ionic conductivity, but also achieve effective interface modification. At the same time, it has excellent mechanical properties, providing a major advancement in silicon anode technology. The cost of polyacrylic acid binder is much lower than that of traditional binder polyvinylidene fluoride. The preparation process of the binder in this application is simple and easy to realize large-scale production and application. The unique functions conferred by pre-lithiation and small molecule interface modification increase the performance of the binder, which can bring certain ideas to the design and synthesis of the binder. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1These are SEM images of the surfaces of the electrode materials of Examples 1 and 4.
[0016] Figure 2 It is the electrode peeling curve diagram and the electrode peeling average strength value diagram of Example 1, Example 4, Example 5 and Example 6.
[0017] Figure 3 It is a diagram of the electrode rate performance of Example 1, Example 4, Example 5 and Example 6.
[0018] Figure 4 In Example 1, Example 4, Example 5 and Example 6, the electrode is at 2.0A g -1 400 cycle performance diagram at a current density of .
[0019] Figure 5 It is a voltage curve diagram of the electrode in Example 1 at different cycle periods.
[0020] Figure 6 The electrode of Example 1 with different surface loadings at 1.0A g -1 50 cycle performance at a current density of .
[0021] Figure 7 It is the CV curve of the electrode of Example 1 in the range of 0.01-1V.
[0022] Figure 8 It is the Nyquist diagram of the electrodes of Example 1, Example 4, Example 5 and Example 6 (the electrodes before being activated).
[0023] Fig. 9 This is the complete XPS spectrum of the electrodes of Example 1 and Example 4.
[0024] Fig.10 is the F / C atomic ratio of the SEI of Example 1 and Example 4. DETAILED DESCRIPTION
[0025] The present application is further described in detail below with reference to the embodiments: Raw material description: All raw materials in the examples can be obtained commercially; in the present application, the purity of silicon nanoparticles is 99.9%, the particle size is 100 nm, and the weight average molecular weight of polyacrylic acid is Mw=250000.
[0026] Example 1 21 mg of polyacrylic acid, 9 mg of oxalic acid and 4.2 mg of lithium hydroxide were weighed separately, dispersed in a reagent bottle containing 2.0 g of deionized water, and stirred at 100°C for 2 hours to obtain a LiPOA component; 140 mg of silicon nanoparticles and 30 mg of conductive carbon black were weighed separately in a black agate mortar, and an appropriate amount of anhydrous ethanol was added to grind into a uniform powder, and then the LiPOA component prepared above was added, stirred for 20 hours, coated, and dried in a vacuum oven at 60°C for 12 hours to obtain a composite electrode sheet.
[0027] Example 2 24 mg of polyacrylic acid, 6 mg of oxalic acid and 4.8 mg of lithium hydroxide were weighed separately, dispersed in a reagent bottle containing 0.8 g of deionized water, and stirred at 100°C for 2 hours to obtain a LiPOA component; 80 mg of silicon nanoparticles and 10 mg of conductive carbon black were weighed separately in a black agate mortar, and an appropriate amount of anhydrous ethanol was added to grind into a uniform powder, and then the LiPOA component prepared above was added, stirred for 20 hours, coated, and dried in a vacuum oven at 60°C for 12 hours to obtain a composite electrode sheet.
[0028] Example 3 27 mg of polyacrylic acid, 3 mg of oxalic acid and 5.4 mg of lithium hydroxide were weighed separately, dispersed in a reagent bottle containing 2.0 g of deionized water, and stirred at 100°C for 2 hours to obtain a LiPOA component; 80 mg of silicon nanoparticles and 10 mg of conductive carbon black were weighed separately in a black agate mortar, and an appropriate amount of anhydrous ethanol was added to grind into a uniform powder, and then the LiPOA component prepared above was added, stirred for 20 hours, coated, and dried in a vacuum oven at 60°C for 12 hours to obtain a composite electrode sheet.
[0029] Example 4 140 mg of silicon powder, 30 mg of polyacrylic acid, and 30 mg of conductive carbon black were weighed into an agate mortar, and an appropriate amount of anhydrous ethanol was added to grind into a uniform powder. Subsequently, the above powder was stirred for 20 hours in a reagent bottle added with 2.0 g of ultrapure water, and then coated and dried in a vacuum oven at 60°C for 12 hours to obtain a composite electrode sheet.
[0030] Example 5 Take 140 mg of silicon powder, 21 mg of polyacrylic acid, and 30 mg of conductive carbon black in an agate mortar, add an appropriate amount of anhydrous ethanol and grind into a uniform powder. Then, stir the above powder in a reagent bottle with 2.0 g of ultrapure water for 20 hours, then coat it, and dry it in a vacuum oven at 60°C for 12 hours to obtain a composite electrode sheet.
[0031] Example 6 140 mg of silicon powder, 30 mg of polyacrylic acid, 6 mg of lithium hydroxide and 30 mg of conductive carbon black were taken in an agate mortar, and an appropriate amount of anhydrous ethanol was added to grind into a uniform powder. Then, the above powder was stirred for 20 hours in a reagent bottle with 2.0 g of ultrapure water, and then coated and dried in a vacuum oven at 60°C for 12 hours to obtain a composite electrode sheet.
[0032] Performance testing The electrode sheet was cut into Φ=12 mm pieces, and the materials were placed in a glove box filled with argon (H2O<0.1ppm, O2<0.1ppm). The negative electrode shell, gasket, steel plate, lithium sheet (counter electrode), diaphragm, electrode sheet, and positive electrode shell were assembled into a battery. The electrolyte was 1 M LiPF6 (EC+DEC 98vol%, FEC 10vol%, VC 1vol%). Subsequently, the R2032 button cell was packaged using a hydraulic sealing machine. The battery was charged and discharged using the Xinwei battery tester CT-4008-5V10mA-164 / CT-4008-5V50mA-S1 at a current density of 0.5A / g, with a voltage range of 0.01-1.2V, and the corresponding capacity-time relationship diagram was obtained to study the lithium storage performance of the electrode material. The button cell was impedance tested using the German Zahner IM-6 electrochemical workstation, with a frequency scan range of 0.1-10 6 HZ, the disturbance voltage amplitude is 5mV. The electrochemical reaction test of the button cell electrode was carried out using the IM-6 model electrochemical workstation of Zahner, Germany, with a scanning voltage range of 0.01-1V and a scanning rate of 0.1mV / s.
[0033] Test results see Figure 1-Figure 10 .
[0034] Reference Figure 1 , (a) is the electrode of Example 4 before cycling, (b) is the electrode of Example 4 after cycling (at 1 A g -1 (c) shows the electrode of Example 1 before the cycle, and (d) shows the electrode of Example 1 after the cycle (at a current density of 1 A g -1 It can be seen that before the cycle, the surface of the electrode of Example 1 (Figure (c)) and the electrode of Example 4 (Figure (a)) is relatively flat and has no cracks, but at 1A g -1After 50 cycles at a current density of , the electrode of Example 4 produced a large number of cracks and had a rough surface (Figure (b)). The gaps between the broken electrodes will cause additional electrolyte to penetrate into the electrode and ultimately accelerate the decomposition of the electrolyte. The electrode of Example 1 had few surface cracks and a smooth surface after cycling, and the electrode structure was relatively complete. This phenomenon is attributed to the superior adhesion and mechanical strength of the LiPOA component. It is precisely because of these outstanding properties of the LiPOA component that it can effectively release the stress generated by the Si negative electrode during the cycle, thereby alleviating the volume expansion problem of the Si negative electrode to a great extent. Based on the above reasons, the structure of the electrode of Example 1 and the electronic and lithium ion channels can maintain a high degree of integrity, which is of great significance for improving the performance and stability of Si-based lithium-ion batteries.
[0035] The 180° peeling test can analyze the strength of the bonding between the binder and the electrode components, which is of great significance for detecting the performance of the binder on Si nanoparticles and current collectors. Figure 2 Among all the electrodes prepared with the adhesives, Example 4 exhibited the lowest peeling force; Example 1 exhibited the highest peeling force. This is because the addition of OA into the adhesive introduced a large number of carboxyl groups, which greatly increased the adhesion of the adhesive, and thus Example 1 exhibited the highest peeling force among all the electrodes.
[0036] Reference Figure 3 , the electrochemical properties of Si-based electrodes with different binders were evaluated using CR2032 coin half-cells. At current densities of 0.4, 1.2, 2, 4, and 8A g-1, the corresponding specific capacities of the electrodes were 3734, 3467, 2964, 2359, and 1557 mAh g-1, respectively. When the current density was reduced to 1.2A g-1, its specific capacity quickly rebounded to 3144 mAh g-1. This phenomenon fully confirms that the electrode of Example 1 not only has excellent kinetic properties, but also has excellent structural stability, can effectively cope with the charging and discharging requirements under different current intensities, and has great potential in high-power application scenarios.
[0037] Reference Figure 4 , showing the cycling performance of binders in different embodiments. At a constant current density of 2A g-1, the electrode in Example 1 still maintains a specific capacity of up to 2044mAh g-1 after 400 cycles and its initial coulombic efficiency is as high as 92.1%, showing excellent cycling durability. In contrast, the capacity of the electrode in Example 4 begins to drop rapidly after about 50 cycles, and the specific capacity is only 101mAh g-1 after 400 cycles.
[0038] Reference Figure 6The electrode with higher surface loading can still stably maintain a surface capacity of 2mAh cm-1 after 50 cycles. The increase in the actual surface loading of the Si electrode is beneficial to improving the energy density of the Si negative electrode battery, which has important practical significance in the application and development of high energy density batteries.
[0039] Reference Figure 7 , in the voltage range of 0.01–1.0V, the CV curve of the electrode of Example 1 exhibits excellent electrochemical stability. Among them, a broad reduction peak appears at 0.17V, which corresponds to the embedding of lithium ions. Two oxidation peaks are shown near 0.36V and 0.53V, corresponding to the two-step extraction process of lithium ions. During the scanning process, the current intensity of the reduction peak (0.17V) and the oxidation peak (0.36V and 0.53V) gradually increased, indicating that the kinetic performance of the electrode gradually increased during the test. In addition, no abnormal peaks appeared at 0.4 and 0.7 V and other positions, indicating that the LiPOA component coating successfully inhibited the decomposition of the electrolyte and the excessive growth of the SEI film.
[0040] Reference Figure 8 , all the curves are composed of obvious high-frequency semicircles and low-frequency oblique lines. Among them, the semicircle in the high-frequency zone is of key significance, representing the charge transfer impedance (Rct). Rct is mainly generated at the interface between the electrode and the electrolyte, accurately reflecting the electrochemical reaction impedance at the electrode-electrolyte boundary. The oblique line in the low-frequency zone corresponds to the Warburg diffusion impedance Wz, which is generated when ions diffuse in the electrode body. By fitting, the Rct values of Example 1, Example 4, Example 6, and Example 5 before the electrode cycle are 78.7Ω, 430.0Ω, 132.1Ω, and 386.0Ω, respectively. Compared with other electrodes, the Rct value of the electrode in Example 1 is the smallest, indicating that the LiPOA component plays an extremely important role in the electrode system and can effectively improve the kinetic performance of the electrode.
[0041] Reference Figure 8 and Fig. 9 The fluorine-carbon (F / C) atomic ratio in the SEI formed by the electrode of Example 1 (F / C = 0.36) significantly exceeds that of the SEI produced by the electrode of Example 4 (F / C = 0.17), indicating that the LiPOA component can induce the formation of a favorable fluorine-rich SEI. The fluorine-rich SEI is strong and has good ionic conductivity, which is effective in improving the cycling performance of the electrode.
[0042] In summary, by pre-lithiation of PAA and grafting OA, the ductility and rigidity of the binder are improved, and the structural stability of the electrode during the cycle is increased to avoid the collapse of the electrode structure. In addition, the addition of OA greatly improves the interface stability of the electrode, which greatly improves the electrochemical stability and cycle stability of lithium-ion batteries.
[0043] This specific embodiment is only an explanation of the present application, and it is not a limitation of the present application. Through the above description, relevant staff can make various changes and modifications without deviating from the technical idea of the present application. The technical scope of the present application is not limited to the content in the specification, and its technical scope must be determined according to the scope of the claims.
Claims
1. A grafted polyhydroxy small molecule lithium ion battery silicon negative electrode binder, characterized in that: Includes silicon nanoparticles, lithium hydroxide and conductive carbon black.
2. A grafted polyhydroxy small molecule lithium ion battery silicon negative electrode binder according to claim 1, characterized in that: Also includes oxalic acid.
3. A grafted polyhydroxy small molecule lithium ion battery silicon negative electrode binder according to claim 2, characterized in that: Also included are polyacrylic acids.
4. A grafted polyhydroxy small molecule lithium ion battery silicon negative electrode binder according to claim 3, characterized in that: The mass ratio of the polyacrylic acid, oxalic acid and lithium hydroxide is 21:(3-9):(4.2-5.4).
5. The method for preparing the grafted polyhydroxy small molecule lithium ion battery silicon negative electrode binder according to claim 4, characterized in that: The steps include: Polyacrylic acid, oxalic acid and lithium hydroxide are dispersed in water, heated and stirred to obtain LiPOA component; silicon powder, conductive carbon black and anhydrous ethanol are mixed and ground to obtain composite powder, and the LiPOA component is added to the composite powder and stirred to obtain the product.
6. The method for preparing a grafted polyhydroxy small molecule lithium ion battery silicon negative electrode binder according to claim 5, characterized in that: When preparing the LiPOA component, the heating and stirring temperature is 100°C.